Pregnancy Outcomes Using Assisted Reproductive Technology After Fertility-Preserving Therapy in Patients With Endometrial Adenocarcinoma or Atypical Complex Hyperplasia. Issue 1 (1st January 2009) - Han, Aera R.; Kwon, Yong-Soon; Kim, D. Y.; Kim, J. H.; Kim, Y. M.; Kim, Y. T.; Nam, J. H.
Abstract : Objectives: To evaluate the outcomes of pregnancy in young women (<40 years old) with early endometrial cancer or atypical complex hyperplasia who were treated by conservative management followed by assisted reproductive technology (ART). Materials and Methods: Medical charts of 11 patients treated from January 1997 to October 2007 at Asan Medical Center were retrospectively reviewed. These patients had all been treated with progestin and serial dilatation and curettage as primary fertility-preserving therapies. Results: After pathological remission of disease, 10 patients tried to become pregnant by ART, 4 by in vitro fertilization and embryo transfer, and 6 by controlled ovarian hyperstimulation, with or without intrauterine insemination. Eight women had intrauterine pregnancies, and 6 patients had live births. Patients have been followed up for 9 to 51 months (mean, 21 months) after delivery, with no evidence of tumor recurrence. Conclusions: Fertility-preserving therapy followed by ART can be a good option in well-selected patients with early endometrial cancer who want to become pregnant.